An analysis of CDS transactions: Implications for public reporting - Kathryn Chen; Michael Fleming; John Jackson; Ada Li; Asani Sarkar (Federal Reserve Bank of New York, 2011)
Ongoing regulatory reform efforts aim to make the over-the-counter derivatives market more transparent by introducing public reporting of transaction-level information, including price and volume of trades. However, to date there has been a scarcity of data on the structure of trading in this market. This paper analyzes three months of global credit default swap (CDS) transactions and presents findings on the market composition, trading dynamics, and level of standardization. We find that trading activity in the CDS market is relatively low, with a majority of reference entities for single-name CDS trading less than once a day. We also find that a high proportion of CDS transactions conform to standardized contractual and trading conventions. Examining the dealer's role as market maker, we find that large trades with customers are generally not rapidly offset by further trades in the same reference entity, suggesting that hedging of large positions, if taking place, occurs over a longer time horizon. Through our analysis, we provide a framework for regulators and policymakers to consider the design of the public reporting regime and the necessary improvements to data collection to facilitate meaningful price reporting for credit derivatives.
Keywords: G12; G18; 330; clearing eligible; credit derivatives; dealer hedging; large trades; price reporting; public transparency; standardization; trade repository